Enhanced OH− Conductivity for Fuel Cells with Anion Exchange Membranes, Based on Modified Terpolymer Polyketone and Surface Functionalized Silica - Narges Ataollahi; Eleonora Tomasino; Oscar Cotini; Rosa Di Maggio (Energies, 2022)
Several modified terpolymer polyketones (MPK) with N-substituted pyrrole moieties in the main chain and quaternized amine in the side group were synthesized for use as anion exchange membranes for fuel cells. The moieties were carried by SiO2 nanoparticles through surface functionalization (Si–N), which were added to the membranes to enhance their overall properties. On increasing the amount of modified silica from 10% to 60% wt/of MPK, there was an increase in Si–N and a corresponding threefold increase in the hydroxide conductivity of the membrane. The MPK–SiN (60%) exhibited a superior ionic conductivity of 1.05 × 10−1 S.cm−1 at 120 °C, a high mechanical stability, with a tensile strength of 46 MPa at 80 °C. In strongly alkaline conditions (1 M KOH, 216 h at 80 °C), the membranes maintained about 70% of the conductivity measured in a usual environment. Fuel cell performance at 80 °C showed a peak power density of 133 mW·cm−2, indicating that using surface-functionalized SiO2 is a simple and effective way to enhance the overall performance of anion exchange membranes in fuel cell applications.